FORMULACIÓN DE UNA NOMENCLATURA UNIFICADA PARA LA ELABORACIÓN DE COLEGIOS INVISIBLES - Peñaranda Ortega, María; Quiñones Vidal, Elena (Anales de Psicología / Annals of Psychology, 2005)
This paper intends to offer a more precise and systematic nomenclature to study invisible colleges than those which exist nowadays. This lack of accuracy occurs because of the absence of a minimum consensus among the authors with respecto to their design. Throughout a method based on the principle of parsimony which provides some simple geometric structures, we can represent the invisible college of any author in a more detailed and precise way, enhancing in this way its research and analysis by other researchers. New concepts such as “defined author”, “direct collaborator” and “close collaborator” appear and all their relationships of union, degree of coauthorship and their development as invisible college along space and time are analysed. Caption planning and planning of the participant institutions in an invisible college are also described precisely.